Education and training of clinical and translational study investigators and research coordinators: A competency-based approach. Issue 1 (13th January 2017) - Calvin-Naylor, Nancy A.; Jones, Carolynn Thomas; Wartak, Michelle M.; Blackwell, Karen; Davis, Jonathan M.; Divecha, Ruthvick; Ellerbeck, Edward F.; Kieburtz, Karl; Koziel, Margaret J.; Luzuriaga, Katherine; Maddox, Jennifer; Needler, Nancy A.; et al.
Abstract : Introduction: Training for the clinical research workforce does not sufficiently prepare workers for today's scientific complexity; deficiencies may be ameliorated with training. The Enhancing Clinical Research Professionals' Training and Qualifications developed competency standards for principal investigators and clinical research coordinators. Methods: Clinical and Translational Science Awards representatives refined competency statements. Working groups developed assessments, identified training, and highlighted gaps. Results: Forty-eight competency statements in 8 domains were developed. Conclusions: Training is primarily investigator focused with few programs for clinical research coordinators. Lack of training is felt in new technologies and data management. There are no standardized assessments of competence.